Cannabidiol as potential anticancer drug. (10th January 2013) - Massi, Paola; Solinas, Marta; Cinquina, Valentina; Parolaro, Daniela
<x xml:space="preserve">Abstract</x> Over the past years, several lines of evidence support an antitumourigenic effect of cannabinoids including Δ9‐tetrahydrocannabinol (Δ9‐THC), synthetic agonists, endocannabinoids and endocannabinoid transport or degradation inhibitors. Indeed, cannabinoids possess anti‐proliferative and pro‐apoptotic effects and they are known to interfere with tumour neovascularization, cancer cell migration, adhesion, invasion and metastasization. However, the clinical use of Δ9‐THC and additional cannabinoid agonists is often limited by their unwanted psychoactive side effects, and for this reason interest in non‐psychoactive cannabinoid compounds with structural affinity for Δ9‐THC, such as cannabidiol (CBD), has substantially increased in recent years. The present review will focus on the efficacy of CBD in the modulation of different steps of tumourigenesis in several types of cancer and highlights the importance of exploring CBD/CBD analogues as alternative therapeutic agents.